Sonography of Scrotal Wall Lesions and Correlation With Other Modalities. (27th May 2017) - Conzi, Raffaella; Damasio, Maria Beatrice; Bertolotto, Michele; Secil, Mustafa; Ramanathan, Subramaniyan; Rocher, Laurence; Cuthbert, Faye; Richenberg, Jonathan; Derchi, Lorenzo E.
Abstract : The scrotal wall may be involved in a variety of pathologic processes. Such lesions may rise primarily from the layers of the scrotum or may be due to a process arising from scrotal content. Imaging is not needed in most cases, but it may be useful for making such differentiations and for evaluation of possible involvement of the testes and epididymides in cases of primary wall abnormalities. This pictorial essay will show the imaging findings observed in a variety of pathologic conditions affecting the scrotal wall, both common and unusual ones, with an emphasis on clinically relevant findings and features that lead to a specific diagnosis.